2020
DOI: 10.24996/ijs.2020.61.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Magnetic Field on Silver Nanoparticles Synthesized by Laser Ablation

Abstract: Laser ablation of a silver target immersed in distilled water using Nd:YAG laser with a fundamental wavelength of 1064nm was carried out to fabricate silver nanoparticles (Ag NPs) with different laser energy in the presence and absence of magnetic field. UV-Visible spectrum showed that the nanoparticles are almost spherical in shape. The number of Ag NPs increased by increasing laser energy while their particle size was reduced by increasing laser energy without magnetic field. In the presence of magnetic fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The added impurities may be associated with increased oxygen vacancies caused by the ZnO: Al lattice, which is the main factor in the gas sensing mechanism [30], [31]. Figures (9) and (10) illustrate the resistance variation of ZnO: Al0.3 wt% and ZnO: Al0.5 wt% samples prepared without and with the magnetic field, respectively, when exposed to 100 ppm concentration of H2S. The AZO-based sensors were tested at different working temperatures (150, 200, 250, and 300 °C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The added impurities may be associated with increased oxygen vacancies caused by the ZnO: Al lattice, which is the main factor in the gas sensing mechanism [30], [31]. Figures (9) and (10) illustrate the resistance variation of ZnO: Al0.3 wt% and ZnO: Al0.5 wt% samples prepared without and with the magnetic field, respectively, when exposed to 100 ppm concentration of H2S. The AZO-based sensors were tested at different working temperatures (150, 200, 250, and 300 °C).…”
Section: Resultsmentioning
confidence: 99%
“…The target properties highly affect the laser-induced nanostructures prepared by the PLD technique [11]. It was found experimentally that using an external magnetic field with the (PLD) technique improves the target ablation process and highly affects the formation of laserinduced nanostructures [10,12,13]. It was reported that applying a tangential magnetic field increases the surface morphology and growth rate of the formed material [14].…”
Section: Introductionmentioning
confidence: 99%
“…They observed that the particle size reduces significantly with an increase in the applied magnetic field and the formation of crystalline nanostructures. Similarly, for Ag NPs, a study was conducted by Abbas et al [171], who observed that the average diameter of the produced particles increased from 14 nm to 25 nm by applying a magnetic field. Similarly, Kim et al [172] observed in their study on Ag NPs that the plasma emission increases with the magnetic field.…”
Section: Magnetic Field-assisted Plalmentioning
confidence: 91%
“…Laser-induced plasma can be confined by different techniques to enhance the plasma breakdown, such as magnetic confinement by applying an external field [37,38],…”
Section: √ ( )mentioning
confidence: 99%